All‐in‐One: Electroactive Nanocarbon as Simultaneous Platform and Label for Single‐Step Biosensing. Issue 24 (6th February 2018) - Cheng, Zhao Xuan; Bonanni, Alessandra
Abstract: We demonstrate here that an electroactive nanocarbon material can simultaneously work as both platform and label for the detection of mycotoxins. The versatility of the material for the immobilization of biorecognition elements was combined with its ability to provide an intrinsic electrochemical signal upon reduction of the oxygen functionalities on its surface. The intensity of peak current reflects the availability of oxygen functionalities for reduction, which can be directly correlated to the specific biorecognition event. We show that the use of electroactive nanocarbon as all‐in‐one biosensing component enables sensitive quantification of Fumonisin B1 (FB1 ) as model mycotoxin analyte, but it can be easily implemented to develop label‐free, cost‐effective and fast bioanalytical devices for universal biosensing. Abstract : Platform and label : Electroactive nanomaterials used as a platform to immobilize biorecognition elements simultaneously provide a working signal for the detection of mycotoxins. A direct correlation between the biorecognition event and the changes in electroactivity of an electroactive nanocarbon platform, enabling precise quantification of the analyte under investigation and good selectivity, is demonstrated.